Mechanotransduction Activity Facilitates Hair Cell Toxicity Caused by the Heavy Metal Cadmium - Schmid, Caleigh; Alampi, Isabella; Briggs, Jay; Tarcza, Kelly; Stawicki, Tamara M. (Frontiers in Cellular Neuroscience, 2020)
Hair cells are sensitive to many insults including environmental toxins such as heavy metals. We show here that cadmium can consistently kill hair cells of the zebrafish lateral line. Disrupting hair cell mechanotransduction genetically or pharmacologically significantly reduces the amount of hair cell death seen in response to cadmium, suggesting a role for mechanotransduction in this cell death process, possibly as a means for cadmium uptake into the cells. Likewise, when looking at multiple cilia-associated gene mutants that have previously been shown to be resistant to aminoglycoside-induced hair cell death, resistance to cadmium-induced hair cell death is only seen in those with mechanotransduction defects. In contrast to what was seen with mechanotransduction, significant protection was not consistently seen from other ions previously shown to compete for cadmium uptake into cells or tissue including zinc and copper. These results show that functional mechanotransduction activity is playing a significant role in cadmium-induced hair cell death.